Institutionalizing Pancasila Values as Strengthening National Character through Standardization of Materials and Methods of Fostering Pancasila Ideology in Informal Education (Family and Society) - Lestanta Budiman; Hastangka Hastangka (Universitas Sebelas Maret, 2021)
The values of Pancasila were introduced as the living values of the community, nation, and state since Pancasila was laid as the foundation of the state and the nation's outlook on life. From the axiological aspect, the values of Pancasila have existed for hundreds of years. These values are then documented in the form of a formula called Pancasila. In the aspect of social, national, and state life, the values of Pancasila began to be institutionalized formally with general standards and criteria by a government policy known as the Pedoman Penghayatan dan Pengamalan Pancasila (P4) containing the guidelines for living and practicing Pancasila values in the 1978s. The implementation of the policy resulted in the formulation of criteria and general standards of Pancasila values known as points of Pancasila. In the period, there were 36 points of Pancasila formulated. Those points of Pancasila are the foundation and guideline in shaping the characters of the citizens, state administrators, and the youth. Ironically, these criteria and standards were abolished in the 1999 reform period. This study will reformulate the institutionalization of Pancasila values for strengthening the national character through standardization of materials and methods of fostering Pancasila ideology in informal education (in family and community). This study was conducted in 2020 through literature studies, focus group discussions with communities, families, and family education experts. The result of this study shows that the institutionalization of Pancasila values in the community and families can be implemented through 8 functions of structural and non-structural families in form of socialization, cultural art media, and innovative methods.